Swarm Optimization-Based Modified Selective Harmonic Elimination PWM Technique Application in Symmetrical H-Bridge Type Multilevel Inverters - Gopal, Y.; Panda, K. P.; Birla, D.; Lalwani, M. (Engineering, Technology & Applied Science Research, 2019)
The problem of elimination of harmonics and the need of a large number of switches in multilevel inverters (MLIs) have been a hot topic of research over the last decades. In this paper, a new variant swarm optimization (SO) based selective harmonic elimination (SHE) technique is described to minimize harmonics in MLIs, which is a complex optimization problem involving non-linear transcendental equation. Optimum switching angles are calculated by the proposed algorithms considering minimum total harmonic distortion (THD) and the best results are taken for controlling the operation of MLIs. The performance of the proposed algorithm is compared with the genetic algorithm (GA). Conventional MLIs have some disadvantages such as the requirement of a large number of circuit components, complex control, and voltage balancing problems. A novel seven-level reduced switch multilevel inverter (RS MLI) is proposed in this paper to recoup the need of a large number of switches. Matlab/Simulink software is used for the simulation of two symmetrical topologies, i.e., a seven-level cascaded H-bridge multilevel inverter (CHB MLI) and a seven-level (RS MLI). Simulation results are validated by developing a prototype of both MLIs. The enhancement of the output voltage waveform confirms the effectiveness of the proposed SO SHE approach.